Puste półki, czyli językowy obraz lat osiemdziesiątych XX wieku w dyskursie współczesnych trzydziestolatków - Biskupska, Kamilla (Empty shelves or linguistic image of the 1980's in the contemporary thirty-year-olds' discourse, 2007)
In this article, the author ponders connection between discourse, ideology, and collective memory. The article contains also part of the author’s research on Polish contemporary thirty year-olds’ discourse. The methodology of the example of data analysis is based on the Discourse Analysis Theory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 268-280